Legal Impact of Criminal Acts on Family Resilience in Gorontalo City - Verawati Arnol; Nopiana Mozin; Lucyane Djaafar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Gambling is a societal issue that negatively affects morality, the economy, and family resilience. This practice can lead to financial loss, domestic violence, and the deterioration of social functions within society. Although gambling is regulated under criminal law in Indonesia, such as Article 303 of the Indonesian Criminal Code and Law No. 7 of 1974, gambling cases continue to rise, including in Gorontalo. This study aims to analyze the legal impact of gambling as a criminal act and how law enforcement is implemented to maintain family resilience. This study uses a qualitative method with a case study approach conducted at the Polres (Kepolisian Resor or Precinct Police Station) of Gorontalo City to examine the legal impact of gambling crimes on family resilience. The findings show that gambling crimes in Gorontalo City, particularly lottery gambling, have fluctuated between 2020 and 2024, with a significant increase in 2023. Gambling has serious impacts on family resilience, causing economic loss, domestic conflict, social stigma, and psychological disorders, especially among children. The main contributing factors include economic pressure, environmental influence, weak supervision, and suboptimal law enforcement. Perpetrators who are repeat offenders, organizers, or who involve others are subject to heavier penalties. The legal impact is not only experienced by the perpetrators but also undermines family stability and causes public concern. Gambling crimes in Gorontalo City have wide- reaching effects, legally disadvantaging the perpetrators and destroying family resilience economically, socially, and psychologically. Key factors such as economic pressure, environmental influence, and weak law enforcement contribute to gambling behavior. As a result, offenders' families experience conflict, stigma, and even household breakdowns. These social impacts create a ripple effect that disrupts community stability.